Color Diversity of Moringa oleifera Plants in Essang Village Based on Morphology - Farneubun, Hana Carolina Elisabeth; Prasetyo, Endry Nugroho (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Moringa (Moringa oleifera) is a nutritionally rich multipurpose plant that is locally cultivated on Poteran Island, Sumenep Regency, where community members in Essang Village traditionally distinguish moringa plants based on petiole color. Based on this local classification, this study aimed to assess the phenotypic diversity and kinship relationships among moringa plants in Essang Village through morphological characterization. Sampling was conducted randomly on ten individual plants, and observed characters included petiole color, leaf apex shape, leaf margin, leaf surface color, stem color, and vegetative organ dimensions. Morphological data were analyzed using MVSP software to generate a dendrogram illustrating kinship relationships. The identification results revealed four petiole-based color groups—white, green, purple, and red—with distinct morphological patterns. Cluster analysis indicated a close kinship relationship between the white and green groups, while the purple and red groups formed a separate cluster. Key distinguishing traits among the groups included petiole color, leaf apex shape, and leaf margin characteristics. Overall, this study demonstrates the presence of local-level phenotypic diversity in M. oleifera populations, providing valuable baseline information for taxonomic studies and supporting local germplasm conservation and sustainable utilization efforts.